A Q-methodology study of parental understandings of infant immunisation: Implications for health-care advice. (November 2015) - Harvey, Hannah; Good, James; Mason, James; Reissland, Nadja
This study used Q-methodology to explore systematically parental judgements about infant immunisation. A total of 45 parents completed a 31-statement Q-sort. Data were collected after vaccination in general practitioner practices or a private day nursery. Q factor analysis revealed four distinct viewpoints: a duty to immunise based on medical benefits, child-orientated protection based on parental belief, concern and distress and surprise at non-compliance. Additionally, there was a common view among parents that they did not regret immunising their children. Implications of these results are discussed in terms of health-care policy and future research.